2020
DOI: 10.1016/j.jtho.2020.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Outcomes of Patients Treated With Re-Irradiation Utilizing Proton Pencil-Beam Scanning for Primary or Recurrent Malignancies of the Esophagus and Gastroesophageal Junction

Abstract: Introduction: Re-irradiation (re-RT) for locoregionally recurrent esophageal and gastroesophageal junction (GEJ) cancer and de novo esophageal þ GEJ cancer arising in-field after a course of prior radiation poses considerable treatment challenges given the sensitivity of surrounding organs at risk (OARs). Guidelines for treatment of this presentation are not well established. Pencil-beam scanning (PBS) proton therapy has the ability to decrease radiation dose to OARs relative to photon plans. We present the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…PBT is expected to achieve a potentially large reduction in cumulative doses to critical OARs, including the spinal cord, heart, lungs, proximal bronchial tree, and liver ( 32 34 ). Several cohort studies have demonstrated feasibility and encouraging early clinical outcomes with PBT reirradiation for EC ( Table 4 ) ( 31 , 33 , 35 , 36 ). Most recently, DeCesaris et al.…”
Section: Clinical Pbt Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…PBT is expected to achieve a potentially large reduction in cumulative doses to critical OARs, including the spinal cord, heart, lungs, proximal bronchial tree, and liver ( 32 34 ). Several cohort studies have demonstrated feasibility and encouraging early clinical outcomes with PBT reirradiation for EC ( Table 4 ) ( 31 , 33 , 35 , 36 ). Most recently, DeCesaris et al.…”
Section: Clinical Pbt Outcomesmentioning
confidence: 99%
“…Another consideration could be superior–inferior posterior oblique beams with the couch at 270°C, which may provide better sparing of normal organs lateral to the target at the expense of delivering higher dose to the spinal cord ( 18 ). Accordingly, most centers treating distal esophagus/GEJ tumors with IMPT have used two to three posterior oriented beams ( 18 , 20 , 33 , 50 ). For treatment of tumors in the cervical and proximal thoracic esophagus, an anterior beam should be considered to reduce lung dose.…”
Section: Pencil Beam Scanning Treatment Planningmentioning
confidence: 99%
“…Additionally, a more recent retrospective study of 17 patients described a lower rate of acute grade 3 toxicity (12%) and no acute grade 4 or 5 toxicities. 17 This lower rate of acute toxicities may be because of the use of pencil beam scanning in the latter report versus passive scattering in the former report. However, in that latter study, DeCesaris et al did report higher rates of late toxicities similar to that in Fernandes et al, with 11.1% grade 3, 12.2% grade 4, and 6.6% grade 5 late toxicities.…”
Section: Discussionmentioning
confidence: 91%
“… 13 , 14 Although proton therapy is increasingly being used in the setting of reirradiation for esophageal cancer, to date, data on outcomes in this patient population are limited to small retrospective 15 and prospective studies, 16 with the largest study reporting outcomes on 17 patients. 17 In this study, we report on outcomes and toxicities from a multi-institutional series of patients with locoregionally recurrent esophageal and GEJ cancers who underwent reRT with PBT.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, all patients but one received protons via the passive scattering technique. Another study generated PBS proton plans for 17 patients with a history of head and neck and thoracic radiation to a median cumulative dose of 104.7 Gy [ 40 ]. The resultant median OS was 19.5 months, with acute and late G3+ toxicity noted in 2 and 5 patients, respectively.…”
Section: Esophageal Cancermentioning
confidence: 99%